Influence of herbicides and nitrogen levels on weed dynamics and durum wheat (Triticum durum desf.) yield - Jat, S.L.; Nepalia, V.; Singh, Dilip; Choudhary, J.; Upadhyay, B. (Annals of Agricultural Research, 2016)
Field trials were conducted during rabi 2007-08 and 2008-09 to find out an appropriate herbicidal recommendation and rate of nitrogen application to augment durum wheat productivity. The twenty seven treatment combinations comprising nine herbicides (weedy check, 2, 4-D at 400 g ha-1, Metsulfuron at 4 g ha-1, Isoproturon at 750 g ha-1, Sulfosulfuron at 25 g ha-1, tank mixtures of 2, 4-D at 400 g ha-1and Metsulfuron at 4 g ha-1 with Isoproturon at 750 g ha-1 and Sulfosulfuron at 25 g ha-1) and three nitrogen levels (60, 90 and 120 kg ha-1) were tested in a split-plot design in three replications. The results revealed that the mixed population of weeds comprising broadleaf and grassy was significantly controlled by applying the herbicide mixtures than their individual applications. The Metsulfuron + Sulfosulfuron mixture resulted in minimum density and dry matter of weeds and NPK uptake by them. The simultaneous increase in NPK uptake by crop by applying this treatment resulted in significantly higher (45.2 & 49.6%) wheat grain yield over weedy check during two respective years of study. The advancing levels of nitrogen over a range of 60 to 120 kg ha-1 were associated with increased NPK uptake by durum wheat and simultaneously significantly higher grain yield by 25.4 & 25.2 % during the two consecutive years of the experiment.